The Influence of Job Satisfaction and Transformational Leadership on Innovative Work Behavior with Knowledge Sharing as a Mediation Variable in Private Bank - Ani, Indri; Arijanto, Agus (Indonesian Journal of Business Analytics, 2024)
The purpose of this observation is to determine whether these factors have an impact on creative work practices among employees of Private Banks. considering that current technological developments have given rise to intense competition in the financial industry. For this reason, the company's human resources are expected to be able to integrate technology into financial practices and create new products. This observation uses a quantitative approach with data analysis methods using SEM PLS. The total population is 343 employees and the sampling technique is random sampling with a total of 185 employees. Observation data was collected through distributing questionnaires. The observation The findings indicate that creative work behavior is positively and significantly impacted by transformational leadership, knowledge sharing, and partial job satisfaction. Knowledge sharing is greatly and favorably impacted by transformational leadership in the workplace satisfaction. Then, the knowledge-sharing variable was proven to be able to serve as a go-between for the relationship between transformative leadership's effects and innovative work practices on job satisfaction.